Impact of Severity of Sickle Cell Anemia on Auditory Discrimination Ability and Speech Perception in Noise - Preeti Sahu; Animesh Barman (International Archives of Otorhinolaryngology)
Introduction Sickle cell anemia (SCA) is a genetic disorder with clinical manifestations due to circulatory changes, leading to adverse effects on the auditory system that might impact auditory processing, such as auditory discrimination and speech perception ability. This condition is associated with the severity level of anemia.